2017
DOI: 10.1093/conphys/cox067
|View full text |Cite|
|
Sign up to set email alerts
|

Being stressed outside the park—conservation of African elephants (Loxodonta africana) in Namibia

Abstract: Human–wildlife interactions are of pressing concern for conservation biologists. We show that African elephants are chronically stressed, have smaller group sizes and may have lower calf recruitment outside of a protected area compared to inside. Additionally, this paper discusses some strengths and weaknesses of using faecal hormone analyses in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 72 publications
4
23
0
Order By: Relevance
“…The French study found that roe deer trade off risk avoidance for food availability and spend more time vigilant during hunting season (Benhaiem et al, 2008). Trophy hunting causes more disturbance to wild mammals than does game viewing and photographic tourism activities, which have comparatively less disturbance on wild mammal behaviour and stress level (Allendorf & Hard, 2009;Hunninck et al, 2017;Lunde et al, 2016;Marealle & Røskaft, submitted;Setsaas et al, 2007). We also found support for our hypothesis that there should be no differences in behaviour between habitats.…”
Section: Behavioursupporting
confidence: 76%
See 3 more Smart Citations
“…The French study found that roe deer trade off risk avoidance for food availability and spend more time vigilant during hunting season (Benhaiem et al, 2008). Trophy hunting causes more disturbance to wild mammals than does game viewing and photographic tourism activities, which have comparatively less disturbance on wild mammal behaviour and stress level (Allendorf & Hard, 2009;Hunninck et al, 2017;Lunde et al, 2016;Marealle & Røskaft, submitted;Setsaas et al, 2007). We also found support for our hypothesis that there should be no differences in behaviour between habitats.…”
Section: Behavioursupporting
confidence: 76%
“…The antipredator behaviour of the RGR impala and greater kudu might have been shaped by game hunting, as we observed larger mean FID there compared to RNP. Hunninck et al (2017) found that elephants are more stressed outside the national park than those within the Etosha National Park in Namibia and Holmern et al (2016) in the Serengeti National Park. Findings by Brown et al (2012) in the Grand Teton National Park in northwestern Wyoming, USA, indicated that elk (Cervus elaphus) and pronghorn (Antilocapra americana) were responsive towards passing vehicles.…”
Section: Behaviourmentioning
confidence: 95%
See 2 more Smart Citations
“…The physiological demands of ranging over long distances can expose animals to stressful environments, making them more susceptible to disturbance (Wilcove & Wikelski, 2008). Negative influences of poaching, human-wildlife conflict, habitat loss, and population fragmentation can affect the physiology of elephants, including reduced reproductive output and increased FGM concentrations (Foley, Papageorge & Wasser, 2001;Gobush, Mutayoba & Wasser, 2008;Graham et al, 2009;Hunninck et al, 2017;Vijayakrishnan et al, 2018). FGM concentrations also have been linked to space use patterns in elephants; that is, the spatial refuge hypothesis, which predicts higher stress in animals with more restricted space compared to those with wider land use patterns (Viljoen et al, 2008;Jachowski, Slotow & Millspaugh, 2012;Jachowski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%